Pathology and pharmacology of lung cancer, stomach cancer and colorectal cancer - Hu, Zihan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cancer, a term that strikes fear and concern in the hearts of millions around the globe, stands as one of the most formidable diseases of our time. It has been responsible for an alarming escalation in the number of fatalities annually, casting a dark shadow over the world’s health statistics. The insidious nature of cancer is further highlighted by the fact that it is no longer confined to the elderly, and it is increasingly affecting younger individuals, defying traditional age-related patterns. However, there is still no cure for cancer, so the development of cancer drugs is particularly important. When looking to the future, the relentless march of technological advancement offers a beacon of hope. With each breakthrough in fields such as genomics, immunotherapy, and nanotechnology, the possibility of defeating cancer is getting closer and closer. This research will cover the history of cancer, introduce three different types of cancer, their pathology and pharmacology.